2005
DOI: 10.1007/s11172-006-0047-z
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic oxidation of olefins and alcohols with hydrogen peroxide in a two-phase system giving mono- and dicarboxylic acids

Abstract: The present study considered the influence of various factors on the catalytic activity of systems based on a combination of tetrakis(oxodiperoxotungsto)phosphate(3-) with quater nary ammonium cations, for example, with methyltri n octylammonium [Me(n C 8 H 17 ) 3 N] + . The catalysts were tested in oxidation of cycloolefins (cyclohexene and cyclooctene), alcohols (octan 1 ol and phenylmethanol), and unsaturated fatty acids (cis 9 octadecenoic and 12 hydroxy 9Z octadecenoic acids) with a 30% hydrogen peroxide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 11 publications
(14 reference statements)
1
49
0
Order By: Relevance
“…These results lead us to conclude that there is no participation of η 2 -peroxo-type (NbO2) complex in the oxidative process, which would lead to the initial formation of an epoxide and subsequently of diols, ketones or carboxylic acids [47,[85][86][87]. In addition, the high degree of oxidation of Nb2O5 should also preclude Fenton-like processes involving hydroxyl radical formation as a reactive species (if formed, these are efficiently quenched by reaction with hydrogen peroxide-forming water and hydroperoxyl radical-before reaching the lipidic carbon chain).…”
Section: Methodsmentioning
confidence: 90%
“…These results lead us to conclude that there is no participation of η 2 -peroxo-type (NbO2) complex in the oxidative process, which would lead to the initial formation of an epoxide and subsequently of diols, ketones or carboxylic acids [47,[85][86][87]. In addition, the high degree of oxidation of Nb2O5 should also preclude Fenton-like processes involving hydroxyl radical formation as a reactive species (if formed, these are efficiently quenched by reaction with hydrogen peroxide-forming water and hydroperoxyl radical-before reaching the lipidic carbon chain).…”
Section: Methodsmentioning
confidence: 90%
“…MO was converted selectively with 97% yield to nonanal and methyl 9-oxononanoate as sole products. Na 3 {PO 4 Pai et al demonstrated the significant influence of the halide anion in the quaternary ammonium salt precursor on the catalytic activity [69]. N-hexadecylpyridinium tetra(diperoxotungsto)phosphate was recognized as suitable catalyst for the cleavage of both OA (86% AA) and RA (84% AA) with 30% aq.…”
Section: Direct Cleavage Of Monoenic Fatty Acids and Estersmentioning
confidence: 99%
“…The method developed by Pai (2005) involves the oxidation of oleic acid with the same oxidizing system H 2 O 2 /Q 3 {PO 4 [WO(O 2 ) 2 ] 4 } as in our process, but with a catalyst formed ex situ, with a treatment performed at room temperature and an extraction of fatty acids with dichloromethane.The second process, developed by Abboud (2011), uses a conventional oxidizing agent, potassium permanganate, and sodium oleate (NaOA) as the substrate. At the end of the reaction, sulfuric acid is added to generate the acids, which are extracted at room temperature with ethyl acetate.…”
Section: Assessment Of the Ecocompatibility Of The Processmentioning
confidence: 99%
“…9. Processes developed by Godard et al (2013a), Pai (2005), and Abboud (2011). OA + O 3 /O 2 → AP + AA+ mixture of by-products…”
Section: Assessment Of the Ecocompatibility Of The Processmentioning
confidence: 99%